Mass measurements on stable nuclides in the rare-earth region with the Penning-trap mass spectrometer TRIGA-TRAP - Ketelaer, Jens; Audi, G.; Beyer, Thomas; Blaum, Klaus; Block, M.; Cakirli, R. B.; Casten, R. F.; Droese, C.; Dworschak, M.; Eberhardt, K.; Eibach, Martin Andreas; Herfurth, F.; et al. (Physical review. C, Nuclear physics, 2011)
The masses of 15 stable nuclides in the rare-earth region have been measured with the Penning-trap mass spectrometer TRIGA-TRAP. This is the first series of absolute mass measurements linking these nuclides to the atomic-mass standard 12C. Previously, nuclear reaction studies almost exclusively determined the literature values of these masses in the Atomic-Mass Evaluation. The TRIGA-TRAP results show deviations on the order of 3-4 standard deviations from the latest published values of the Atomic-Mass Evaluation 2003 for some cases. However, the binding-energy differences that are important for nuclear structure studies have been confirmed and improved. The new masses are discussed in the context of valence proton-neutron interactions using double differences of binding energies, δVpn(Z,N).
Gesehen am 01.08.2022